Uçá crab residues addition, Ucides cordatus (Linnaeus, 1763) in concrete for precast: sustainability for the productive chain actors on the north coast of the Brazilian Amazon (Research, Society and Development, 2020)
In the context of reducing the inappropriate waste disposal from the uçá-crab processing activity in the coastal zone of the Brazilian Amazon, the objective of this research was to produce and evaluate the mechanical strength of concrete with the addition of the exoskeleton (carapace) powder of the uçá-crab, at different levels of inclusion. Data on volume and composition of waste generated was collected from in loco visits. Five strokes were formulated and analyzed with different levels of inclusion (5, 10, 15 and 20%) of addition of crab shell powder to replace the fine aggregate mass (sand), seeking a mechanical resistance to axial compression of 25 Mpa at 28 days of age. The proximate (ou chemical) composition of the uçá crab shell powder indicated the percentages of: 8.73 moisture, 69.89 ash, 16 protein and 0.4 lipids. The concrete with the addition of 5% showed no significant difference in relation to the reference trace. Concrete with an addition of 10% showed a reduction of 35.12% in relation to the reference trace. Formulations with 15% and 20% addition reduced the resistance by 57.11% and 70.13%, respectively, when compared to the reference trace. It is concluded that the concretes with 5% and 10% inclusion reached resistance values ​​indicated for making precast (17 Mpa); for the levels of 15 and 20% of inclusion, there was a significant loss of resistance, indicating the need for research to indicate the appropriate use of concretes with the levels of resistance presented.